Comparison of the TLR4/NFκB and NLRP3 signalling pathways in major organs of the mouse after intravenous injection of lipopolysaccharide - Qin Gong; Luling He; Mulan Wang; Shasha Zuo; Hongwei Gao; Yulin Feng; Lijun Du; Yingying Luo; Jun Li (Taylor & Francis Group, 2019)
Context: Lipopolysaccharide (LPS) is often used to induce immunoinflammatory reactions. TLR4/NFκB and NLRP3 signalling are major factors for inflammation. Dexamethasone (DXM) has an anti-immunoinflammatory effect. Objective: To investigate the inflammatory reaction in pathological changes of organs and the expression of inflammatory signalling during LPS infection. Materials and methods: ICR mice were divided into control group (n = 9), LPS group (n = 15) and LPS + DXM group (n = 14). LPS (10 mg/kg) was injected intravenously in LPS group and LPS + DXM group, normal saline was injected to the control group; DXM (0.5 mg/kg) was given by intragastric administration. 12 h after LPS, the blood was collected and the organs were isolated for biochemical analysis, protein expression, and morphological examination. Results: The results showed that BUN, Cre, ALT, AST in the LPS group increased distinctly by 81.42, 67.84, 40.53 and 36.05%, respectively, and CK, ALP, TP and ALB decreased by 71.37, 60.6, 12.57 and 19.73%, respectively, compared with the control group. In the morphologic observation, local necrosis in the liver, arterial vasodilation in the heart and kidney, alveolar secretions and pulmonary interstitial in the lungs, and mucosal shedding in the small and large intestines, the expression of TLR4-NFκB signalling were up-regulated distinctly whereas NLRP3 signalling was less broadly affected. DXM can decrease BUN and Cre, downregulate the expression of TLR4-NFκB signalling, but has no effect on the organ damage based on morphology. Conclusion: Acute injuries induced by LPS are extensive. The inflammatory damage in small and large intestines, liver and kidney was more severe than other organs. TLR4-NFκB signalling was the major response to LPS stress.